Application of Gum Arabic and Drying Temperature in Aloe-Buni Instant Drink - Luh Suriati; B Elopere; AASM Chindrawati; NLPSD Damayanti (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Aloe-buni is a functional drink made from aloe vera extract and buni fruit, rich in fiber and antioxidants that are beneficial to health. The purpose of this study was to determine the use of gum arabic and variations in drying temperature on aloe-buni powdered drinks. This study used a complete randomised design (CRD) factorial with two treatment factors: gum arabic filler concentrations of 10%, 20%, and 30%, and drying temperatures of 30°C, 40°C, and 50°C. The results of the study show that the best filling material and drying temperature to maintain the characteristics of Aloe-Buni powdered drink are 30% gum arabic concentration and 40°C heating temperature, which produce the best Aloe-Buni powdered drink with a pH of 4.30; TSS of 41.33°Brix; L* color of 40.92; a* color of 4.86; b* color of 6.71; moisture content of 5.61%; solubility of 98.56%; antioxidant activity of 7.46%; and vitamin C of 66606.44 mg/100ml. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 3: Good Health and Well-BeingSDG 9: Industry, Innovation and InfrastructureSDG 12: Responsible Consumption and Production